2007
DOI: 10.1128/jvi.02584-06
|View full text |Cite
|
Sign up to set email alerts
|

Cytidine Deaminases APOBEC3G and APOBEC3F Interact with Human Immunodeficiency Virus Type 1 Integrase and Inhibit Proviral DNA Formation

Abstract: APOBEC3G (A3G) is a single-stranded DNA cytidine deaminase that targets retroviral minus-strand DNA and has potent antiviral activity against diverse retroviruses. However, the mechanisms of A3G antiviral functions are incompletely understood. Here we demonstrate that A3G, A3F, and, to a lesser extent, the noncatalytic A3GC291S block human immunodeficiency virus type 1 (HIV-1) replication by interfering with proviral DNA formation. In HIV-1 virions, A3G interacted with HIV-1 integrase and nucleocapsid, key vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
183
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(200 citation statements)
references
References 65 publications
(64 reference statements)
16
183
1
Order By: Relevance
“…Some of these effects do not require catalytically active APO3G (19,22), and several reports suggested that deaminase-defective APO3G and APO3F have antiviral activity when transiently coexpressed with HIV-1 in 293T cells (3,12,28,35). Our own data concerning the antiviral properties of the deaminase-defective APO3G C288S/C291A mutant supported these conclusions (30).…”
supporting
confidence: 78%
See 3 more Smart Citations
“…Some of these effects do not require catalytically active APO3G (19,22), and several reports suggested that deaminase-defective APO3G and APO3F have antiviral activity when transiently coexpressed with HIV-1 in 293T cells (3,12,28,35). Our own data concerning the antiviral properties of the deaminase-defective APO3G C288S/C291A mutant supported these conclusions (30).…”
supporting
confidence: 78%
“…On the other hand, the single-round infectivity assay used in our studies is relatively insensitive to such APO3G-induced mutations since it requires only the production of functional Tat protein (31). Thus, the cytidine deaminase-induced loss of viral infectivity is more likely explained by effects on DNA stability or other effects such as the reported inhibition of tRNA-primed reverse transcription (9), inhibition of plus-strand transfer (26), or inhibition of integration (22,26).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Because of the difficulties in detecting eqA3-derived cytidine deamination in EIAV genomes, we studied the relevance of the zinc coordination domain for the antiviral activity. It has been reported that cytidine deamination is largely dispensable for the inhibition HIV-1 ⌬vif by human A3F and A3G (4,30,46,61). But controversially, several groups have reported a significant drop in inhibition observed when active-site mutants of human A3G were analyzed (8,9,22,23,56,75).…”
Section: Vol 83 2009 Restriction Of Eiav By Apobec3 7551mentioning
confidence: 99%